Modelling and Testing the Dynamic Properties in a Submachine Gun-Man System - Zbigniew J. DZIOPA (Modelowanie i badanie dynamicznych właściwości układu strzelec-pistolet maszynowy, 2023)
This work was an attempt at an analysis of the interaction between a firearm and a human, exemplified by a cal. 9 mm submachine gun (SMG), PM-98 GLAUBERYT and a trained, professional shooter – a Police special team operator. The results of the analysis made it possible to develop several guidelines aimed at designing the dynamic performance of SMGs to improve their aiming accuracy. In connection with this work, experimental tests were performed at a firing range, where the process of firearm discharge was recorded using a Phantom slow-motion digital camera. What followed was the analysis of the video record using the Tema dedicated computer software. The SMG’s dynamic performance was adjusted to reduce the hit scatter. Based on the results of the empirical tests at the firing range, physical and mathematical models of the SMG-operator system were formulated. The SMG-operator system was simulated in the Scilab software, which provided time-based variation trends of the kinematic quantities that characterised the movements of individual modelled objects. The variation trends determined included displacement, velocity and acceleration of the SMG, its bolt assembly, and the human operator as a function of time. The results of the theoretical analysis were compared to the empirical test results from the firing range. It was found that in the virtual modelling space, the SMG model had a performance similar to that of its real counterpart. With the theoretical model verified, several performance parameters of the SMG were modified and guidelines were developed that could improve the aim.
Keywords: Dynamika ukladu strzelec-pistolet maszynowy